2003
DOI: 10.1002/app.13284
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of PET/silica nanocomposites

Abstract: Poly(ethylene terephthalate) (PET)/silica nanocomposites were fabricated by direct polymerizing PET monomer dispersed with organic modified silica nanoparticles. The characteristics and properties of these nanocomposites were investigated by the transmission electron microscopy, differential scanning calorimetry, and thermogravimetric analysis, respectively. The results show that (1) the nanoparticles have been well dispersed in the polymer matrix; (2) the addition of nanoparticles can speed up the crystalliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 28 publications
(26 reference statements)
5
60
0
Order By: Relevance
“…The homogeneous dispersion of nanoscale particles in the polymer matrices and the good interfacial interaction between them are the key points to the fascinating properties exhibited by polymer/ inorganic nanocomposites. Several methods have been developed to prepare polymer/inorganic nanocomposites, including in situ polymerization [3,4], melt-blending/ extrusion [5] or solution blending [6]. Among these methods, in situ polymerization has been proved to be an effective way to prepare high-performance nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…The homogeneous dispersion of nanoscale particles in the polymer matrices and the good interfacial interaction between them are the key points to the fascinating properties exhibited by polymer/ inorganic nanocomposites. Several methods have been developed to prepare polymer/inorganic nanocomposites, including in situ polymerization [3,4], melt-blending/ extrusion [5] or solution blending [6]. Among these methods, in situ polymerization has been proved to be an effective way to prepare high-performance nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…15 The same result has been observed in the report of Liu et al studying poly(ethylene terephthalate) (PET)/silica nanocomposites. 16 In this study, the increase of T c is suggested that the silica nanoparticles result in the change from homogeneous nucleation to heterogeneous nucleation. In the case of heterogeneous nucleation resulting from the foreign materials, it is well known that T c tends to increase due to the nucleating effect of the materials.…”
Section: Resultsmentioning
confidence: 74%
“…Zheng and Wu (2007) in their study have shown that nanosilica do not behave as a nucleating agent but rather retard the appearance of the microcrystalline phase that enhances spinnability. Liu et al (2004) have found that the addition of nanoparticles increases the crystallization temperature and the melting point of the polymer.…”
Section: From Kementrian Kelautan Dan Perikanan (Ocean and Fisheries mentioning
confidence: 99%